Cost-Benefit Analysis Program Percontohan Pengendalian Rabies Berbasis One Health di Wilayah Sanur, Denpasar Selatan - Ni Wayan, Marheni; I Nyoman, Sutarsa; Subrata, Made (Jurnal Ekonomi Kesehatan Indonesia, 2025)
Rabies continues to pose a significant public health challenge in Bali Province, Indonesia. The Dharma Program, a rabies control initiative based on the One Health approach, has been implemented in multiple areas of the province. Sustaining and expanding this program requires an economic evaluation that compares the cost burden of rabies under scenarios with and without program implementation. This study was conducted in two pilot villages: Sanur Kaja (SKJ) and Sanur Kauh (SKH). Cost data were obtained from activity reports, published literature, and structured interviews with program managers. Benefit values were estimated using scenario modeling, which included treatment costs, post-exposure prophylaxis (PEP) expenses, costs for examining suspected rabid dogs, and vaccination costs for rabies-transmitting animals. The analysis utilized net present value (NPV) and benefit-cost ratio (BCR) as economic indicators. In both villages, the program achieved economic efficiency under conditions of high incidence of bites from rabies-transmitting animals (RTA), as indicated by positive NPV and BCR values greater than one in the third year. Specifically, Sanur Kaja reported an NPV of IDR 21.3 million and a BCR of 1.19, while Sanur Kauh (SKH) reported an NPV of IDR 28.8 million and a BCR of 1.43. Under scenarios of low RTA incidence, both villages experienced negative NPV and BCR values below one, although the magnitude of these losses declined annually. Key variables affecting program financing included the proportion of dogs sterilized, rabies vaccination costs, PEP prices, and changes in RTA incidence. The Dharma Program has demonstrated potential economic efficiency, with positive NPV and BCR achieved from the third year. The continuously improving NPV values and initial investments in dog sterilization and community education contributed to reducing long-term vaccination costs. However, since the analysis remains internal and has not been compared with alternative programs, further comparative studies are required.